Cultivo e conservação in vitro de sempre vivas - Moreira, Fernanda da Conceição (2015)
Comanthera bisulcata (Eriocaulaceae) and Xyris cipoensis (Xyridaceae) are ornamental species, occurring in campos rupestres environments and are on the endangered list species. The aim of this study were: (i) in vitro establishment, control of senescence and the multiplication of Comanthera bisulcata seedlings. (ii) micropropagation and (iii) conservation in vitro of Xyris cipoensis. To establish in vitro C. bisulcata was performed seeds sterilization at different times immersed in NaOCl. The germination and growth of seedlings were evaluated in WPM medium with different pH. For the control of senescence were tested 0, 0.2, 2 and 20 µM AgNO3 and the oxidation control was tested from 0 to 400 mg L-1 of polyvinylpyrrolidone (PVP). The multiplication was tested 2.68 µM NAA + 2.27 µM TDZ, 2.22 µM BA or 2.32 μM KIN. Subsequently, an experiment was conducted comparing the semi-solid system and the temporary immersion system (Plantform®). The Xyris cipoensis seeds were decontaminated in different exposure times NaOCl. The WPM medium with different sucrose concentrations was tested. The seeds were stored in liquid nitrogen. Thawing was performed at different times. Subsequently, the seeds were dried at different times, cryopreserved and thawed for 60 seconds. In C. bisulcata the highest percentage of disinfestation (96%) and germination (54%) of the seeds was observed in five minutes immersion in NaOCl. Seedlings grown at pH 4.4 showed higher average root length (1 cm) and greater average height (2.8 cm) of seedlings. During the proliferation phase, the seedlings senescence can be reduced with 0.2 M AgNO3 and the oxidation with 400 mg L-1 antioxidant polyvinylpyrrolidone and 2.68 µM NAA + 2.27 uM TDZ was suitable to induce shoots. The relative growth rate (RGR) and average values average weight of seedlings demonstrated the superiority of temporary immersion system liquid (Plantform®) comparing to the semi-solid system during micropropagation C. bisulcata. The highest percentage of decontamination and germination (90% and 84%) was observed after five minutes of exposure to NaOCl and using 15g L-1 sucrose, respectively. An efficient protocol for the in vitro propagation was obtained and increased post-thaw viability of cryopreserved seed was reached after thawing for 60 seconds. Survival seeds increased when seeds were dehydrated before cryopreservation process.